African American Folk Healing. - Mitchem, Stephanie (NYU Press, 2007)
Cure a nosebleed by holding a silver quarter on the back of the neck. Treat an earache with sweet oil drops. Wear plant roots to keep from catching colds. Within many African American families, these kinds of practices continue today, woven into the fabric of black culture, often communicated through women. Such folk practices shape the concepts about healing that are diffused throughout African American communities and are expressed in myriad ways, from faith healing to making a mojo. Stephanie Y. Mitchem presents a fascinating study of African American healing. She sheds light on a variety o.